Threshold evaluation for optimal number of endoscopic treatment sessions to achieve complete eradication of Barrett’s metaplasia - Mittal, Chetan; Muthusamy, V. Raman; Simon, Violette C.; Brauer, Brian C.; Mullady, Daniel K.; Hollander, Thomas; Sloan, Ian; Kushnir, Vladimir; Early, Dayna; Rastogi, Amit; Hammad, Hazem T.; Edmundowicz, Steven A.; Han, Samuel; Thaker, Adarsh M.; Ezekwe, Ezenwanyi; Wani, Sachin; Kwasny, Mary J.; Komanduri, Srinadh (Endoscopy, 2022)
Background Endoscopic eradication therapy (EET) is the standard of care for Barrett’s esophagus (BE)-associated neoplasia. Previous data suggest the mean number of EET sessions required to achieve complete eradication of intestinal metaplasia (CE-IM) is 3. This study aimed to define the threshold of EET sessions required to achieve CE-IM.Methods The TREAT-BE Consortium is a multicenter outcomes cohort including prospectively enrolled patients with BE undergoing EET. All patients achieving CE-IM were included. Demographic, endoscopic, and histologic data were recorded at treatment onset along with treatment details and surveillance data. Kaplan–Meier analysis was performed to define a threshold of EET sessions, with 95 %CI, required to achieve CE-IM. A secondary analysis examined predictors of incomplete response to EET using multiple logistic regression and recurrence rates.Results 623 patients (mean age 65.2 [SD 11.6], 79.6 % male, 86.5 % Caucasian) achieved CE-IM in a mean of 2.9 (SD 1.7) EET sessions (median 2) and a median total observation period of 2.7 years (interquartile range 1.4–5.0). After three sessions, 73 % of patients achieved CE-IM (95 %CI 70 %–77 %). Age (odds ratio [OR] 1.25, 95 %CI 1.05–1.50) and length of BE (OR 1.24, 95 %CI 1.17–1.31) were significant predictors of incomplete response.Conclusion The current study found that a threshold of three EET sessions would achieve CE-IM in the majority of patients. Alternative therapies and further diagnostic testing should be considered for patients who do not have significant response to EET after three sessions.